Antagonism Pseudomonas diminuta on The Growth of Vibrio harveyi with Mix Culture Method - Dr. Woro Hastuti Satyantini, Ir., M.Si; Ahmad Syahrul Mubarak; Sri Subekti (Department of Aquaculture, 2023)
One of the obstacles often encountered in white shrimp farming is the presence of bacterial diseases caused by Vibrio group bacteria. One of the efforts to control Vibriosis is by using antagonistic bacteria as biocontrol agents, one of which is using Pseudomonas diminuta. In this study Pseudomonas diminuta and Vibrio harveyi were co-cultured with the aim of determining the optimal density and effective incubation time of P. diminuta which could provide the highest inhibition of V. harveyi growth. This study used a completely randomized design with six treatments P0 (P. diminuta 105 CFU/ml), P1 (V. harveyi 106 CFU/ml), P2 (P. diminuta 105 CFU/ml+V. harveyi 106 CFU/ml), P3 (P. diminuta 106 CFU/ml+V. harveyi 106 CFU/ml), P4 (P. diminuta 107 CFU/ml+V. harveyi 106 CFU/ml), P5 (P. diminuta 108 CFU/ml+V. harveyi 106 CFU/ml). The results of this study showed that P2, P3, P4 and P5 had decreased growth of V. harveyi when compared to control P1 (V.harveyi 106 CFU/ml). The decrease in the growth of V. harveyi occurred at the 8th to 48th hour. V. harveyi in P3 (2.72 × 108 CFU/ml), P2 (2.80 × 108 CFU/ml), P4 (2.96 × 108 CFU/ml) and P5 (2.90 × 108 CFU/ml) at the 48th hour of incubation was lower than P1 (3, 15×108 CFU/ml). Based on the results of the Duncan test showed that P2, P3, P4 and P5 were significantly different (p <0.05) from P1. From this study it was concluded that administration of P. diminuta at a density of 106 CFU/ml was able to reduce the growth of V. harveyi. The greatest decrease in the growth of V. harveyi occurred at the 48th hour.